Knowledge and Attitude among Doctors towards Use of Prophylactic Vitamin K in Neonatal Bleeding Disorders in Department of Obstetrics and Gynecology: Experience from Haj El-Safi Hospital, Sudan - Rawan Mohamed Sabri Hassan; Abrar Bakry Malik; Mohamed Eltayeb Elawad; Ebtihal Modather Mohammed; Ahmed Sami Abdalla Osman (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Vitamin K is crucial for neonates to prevent bleeding disorders. Raising awareness of vitamin K use would show positive outcomes. This study aimed to assess the knowledge and attitude of prophylactic use of vitamin K for bleeding disorders in neonates among doctors working in the Department of Obstetrics and Gynecology at Haj El-Safi Hospital, Sudan.Methods: A descriptive cross-sectional study was conducted in February 2019, involving 36 doctors selected by convenience sampling. Data were collected by an interview-based questionnaire designed to measure the knowledge level of doctors toward vitamin K deficiency classification and interactions, guidelines availability and adherence, and parents counseling. Data were analyzed and presented in tables. Results: The doctors involved in this study were 36, including 7 registrars, 6 medical officers, 23 house officers, mostly aged 20–25 years (n=29), and female (n=27). The level of knowledge about the classification of vitamin K deficiency and the interaction of vitamin K with other drugs among doctors was mostly good (n=14 and n=15, respectively). Registrars were the most in the good category (n=6, and n=7, respectively). Most doctors (n=23) were aware of vitamin K guidelines, while only 15 have continuous adherence, 16 of doctors counseled parents about the importance of prophylactic vitamin K.Conclusion: The level of knowledge towards prophylactic vitamin K use in neonatal bleeding disorders among doctors in the Department of Obstetrics and Gynecology at Haj El-Safi Hospital is good.